Interaction patterns for concurrently executed parallel tasks - Dümmler, Jorg (Proceedings of the Conference Algoritmy, 2015)
Large parallel applications often consist of multiple program parts that can be implemented separately in form of parallel modules. The interactions between these modules can be captured by a high-level coordination structure. This coordination structure represents the data flow within the parallel application and denes restrictions of the execution order of the parallel modules. The coordination structure of an application can be dened independently of the modules using a high-level specication language. This article focuses on possible interactions between concurrently executed parallel modules that have to exchange data during their execution. For this purpose, several interaction patterns are considered and their denition in the specication language is illustrated. An experimental evaluation using dierent application benchmarks underlines the feasibility of the programming approach and shows the use of the interaction patterns.